Industrial application as utility requirement and the future of Malaysian biotechnology industry - Mohamed Yusof, Nor Ashikin (2013)
Patent law only protects practical works of arts and not ideas or concept. This has always been the basis of the second pa - tentability requirement. Philosophically it is to separate basic research science from applied science, avoids protecting pre- mature, unwarranted, frivolous or injurious invention. Pro - cedurally inventor must demonstrate the specific function, practical benefits and how to use the invention. Otherwise he must conduct further research to perfect the invention un - til the real utility, capabilities and parameters of the same are known finally.